Personal and Vicarious Experiences that Shape Incarcerated Youths’ Perceptions of Injustice- Comparing Two Measures - Hartsell, Elizabeth (Victims & offenders, 2023)
We compared the relationships between incarcerated youths’ injustice perceptions and demographic variables and personal and vicarious experiences with the justice system using indexes of injustice derived from Matza and Tyler. The two injustice frameworks represent different academic traditions in ways that raise different prospects. Matza contextualizes his formulation of injustice in group processes that emphasize shared neutralization of regulating norms because of injustice. That emphasis is absent in Tyler. Tyler’s work has led to an invariance claim across demographics that is not postulated by Matza. We analyzed data from the Florida Faith and Community-Based Delinquency Treatment Initiative. We found nonwhite youths perceived more injustice as measured by both indexes. In a boys-only subsample, younger boys perceived more injustice measured by the Tyler index. Vicarious exposure via friends’ experiences with police related to higher perceived levels of injustice only on the Matza index. We encourage researchers to be precise in their operationalizations and measurement of injustice perceptions and to consider the theoretical grounding of their research in making injustice measurement choices.